Short sleep duration is associated with higher risk of central obesity in adults: A systematic review and meta‐analysis of prospective cohort studies - Ali Kohanmoo; Masoumeh Akhlaghi; Najmeh Sasani; Fatemeh Nouripour; Caterina Lombardo; Asma Kazemi (Wiley, 2024)
Abstract Background and Objective The relationship between sleep duration and obesity has been the focus of numerous investigations. This systematic review and meta‐analysis of prospective cohort studies aimed to assess the relationship between sleep duration, abdominal obesity, and body composition. Methods PubMed, Scopus, and Web of Science were searched until February 2024. Cohort studies that assessed the relationship between sleep duration at night and central obesity measures or body composition indices in adults were included. The quality of studies was assessed using the Newcastle‐Ottawa scale. Random‐effects meta‐analysis was conducted on studies that reported risk ratio (RR) and 95% confidence intervals (CIs). Results Eighteen studies were eligible to be included. Eleven out of the 18 studies were not included in the analysis as 10 studies did not report RR, and in one study, the definition of short and normal sleep duration was different from others. The results of the meta‐analysis indicated that short sleep duration was significantly associated with abdominal obesity (RR = 1.08; 95% CI: 1.04-1.12; I2 = 49.1%, n = 7), but long sleep duration was not (RR = 1.02; 95% CI: 0.83-1.24; I2 = 98.2%, n = 6). Conclusions Short sleep duration was associated with a slightly higher risk of central obesity, while long sleep duration was not.